Modeling of Solar PV System - , J. Vijaychandra; G. Reshma, M. Sai Sandeep, A. Janardhan, B. Gowtham (Journal of Power Electronics and Devices, 2021)
The necessity of power demand is increasing in the world and thereby a question arises what if conventional energy resources are going to be extinct in the future. The best alternative for the above mention question is to make use of non-conventional energy resources like Solar, Wind, Hydro, fuel cell, etc. For the increase in power, the individual energy systems are being combined to form a hybrid system. This paper addresses the Modeling of a PV system by using MATLAB/Simulink Software. To maximize the power from the PV system, an MPPT controller will be used, and, in this paper, Perturb and Observe Method is used and a boost converter is used to boost the output voltage of the PV module.